Effects of Spirulina platensis on neuropathic pain in Wistar rats - Shahnaz, Monira; Biswas, Parijat; Akhter, Masuma; Rafiq, Kazi; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2021)
Background: In treatment of neuropathic pain, conventional analgesics showed various adverse effects. Spirulina platensis (Sp), a medicinal herb, shown to possess several beneficiary biological activities including analgesic, anti-inflammatory and anti-ulcerogenic potential. Objectives: To assess the effect of Sp on neuropathic pain in Wistar rats and also to assess the involvement of ATP sensitive potassium channel (KATP) as its possible underlying mechanism of action. Methods: For this experimental study 120 Wistar rats of both sexes (200±50 gm body weight) were grouped into control [normal saline (NS) 5 ml/kg/day], sham control [sham surgery + NS], CCI control [Chronic constriction injury to sciatic nerve (CCI) + NS], Sp experimental [CCI + Sp 400 mg/kg/day], Gli experimental [CCI + Sp (400 ml/kg/day) + glibenclamide (15 mg/kg)] groups. Sp and NS were administered orally once daily for consecutive 21 days and single dose of glibenclamide was given intraperitoneally. Then again on the basis of neuropathic pain evaluation tests, all the groups were subdivided into ‘a’ (for walking track analysis), ‘b’ (for cold tail immersion test), ‘c’ (for von Frey test), ‘d’ (for hot plate test). The statistical analysis was done by one-way ANOVA followed by Bonferroni post hoc test, where P£0.05 was considered as statistically significant. Results: In this study, Sp showed significantly (P£0.001) higher sciatic functional index, tail flick latency, paw withdrawal threshold and reaction time in Sp experimental rats compared to those of CCI control rats. In addition, there were significant (P£0.001) differences in the above-mentioned variables between rats of Sp experimental group and Gli experimental group. Conclusion: From the present study it could be concluded that, Spirulina platensis prevents the development of neuropathic pain in Wistar rats through opening of KATP channel. J Bngladesh Soc Physiol 2021;16(1): 1-10